Pelatihan Branding Equity untuk Membangun Brand Image pada Pelaku UMKM di Desa Ciawi dalam Meningkatkan Daya Jual: Branding Equity Training to Build Brand Image for MSME Actors in Ciawi Village in Increasing Selling Power - Deva Ariyani; Slamet Bambang Riono; Hendri Sucipto (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2022)
The development of MSMEs is currently influential in increasing people's income, facilitating and accelerating the process of improving the economy. MSME actors in Ciawi village are still done manually by taking orders offline. This is done because they still have little energy and limitations to market these products, and lack of mastery of information and communication technology-based marketing strategies. This community service aims to provide the community with the importance of brand strength of a product brand (brand equity) of SMEs, and how to introduce the brand so that it is known to all levels of society. Most of the GENERAL actors in Ciawi village have not used good and attractive packaging, do not know a place where they can become legal entrepreneurs and develop better through MSME groups in the Brebes Regency area. Furthermore, the team formulated problem analysis and solutions related to problems in the field by providing branding equity training which was attended by 20 participants. In addition, training on making packaging that is more attractive, to support buying interest and selling power. Marketing strategy introduced by utilizing the use of social media to support business development activities.